Connecting Structural and Transport Properties of Ionic Liquids with Cationic Oligoether Chains. Issue 8 (1st January 2017) - Lall-Ramnarine, Sharon I.; Zhao, Man; Rodriguez, Chanele; Fernandez, Rahonel; Zmich, Nicole; Fernandez, Eddie D.; Dhiman, Surajdevprakash B.; Castner, Edward W.; Wishart, James F.
Abstract : X-ray diffraction and molecular dynamics simulations were used to probe the structures of two families of ionic liquids containing oligoether tails on the cations. Imidazolium and pyrrolidinium bis(trifluoromethylsulfonyl)amide ILs with side chains ranging from 4 to 10 atoms in length, including both linear alkyl and oligo-ethylene oxide tails, were prepared. Their physical properties, such as viscosity, conductivity and thermal profile, were measured and compared for systematic trends. Consistent with earlier literature, a single ether substituent substantially decreases the viscosity of pyrrolidinium and imidazolium ILs compared to their alkyl congeners. Remarkably, as the number of ether units in the pyrrolidinium ILs increases there is hardly any increase in the viscosity, in contrast to alkylpyrrolidinium ILs where the viscosity increases steadily with chain length. Viscosities of imidazolium ether ILs increase with chain length but always remain well below their alkyl congeners. To complement the experimentally determined properties, molecular dynamics simulations were run on the two ILs with the longest ether chains. The results point to specific aspects that could be useful for researchers designing ILs for specific applications.